Arouj policy in liberating Algerian cities from the Spanish occupation 1500-1518AD - صقر ولاء (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
This study examines the policy of Arouj and its role in the face of the Spanish project, which aims to occupy the cities and ports of Algeria for a number of reasons, the most important of which is the communication between the Muslims of Andalusia and Algeria and securing the commercial route of the sea, which reaches the coasts of the Italian coasts and its islands in the Mediterranean, but the project failed due to the emergence Aruj, who managed to help his brother Khairuddin to confront the Spanish occupation and liberate many of the Algerian cities to be studied in the study, thus ending the reign of Arouj by establishing a strong and despicable state later ruled by his brother Khairuddin Belerbaya on Algeria with the support of The Ottoman state